2019
DOI: 10.1016/j.foodres.2018.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the killing method of the black soldier fly on its lipid composition

Abstract: Black soldier fly (BSF, Hermetia illucens) represents a valuable source of biomolecules and it also constitutes an economic way to valorise residual biomasses. BSF prepupae contain high amounts of lipids (37% DM basis). The present investigation aimed at studying the composition of BSF lipids and the effect of killing/storage on their quality. The main fatty acid was lauric acid, sterols were represented primarily by beta-sitosterol and campesterol. Global fatty acid and sterol profiles, determined by GC-MS, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
64
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 37 publications
8
64
1
Order By: Relevance
“…These insects were killed rapidly (30 min at − 20 °C followed by nitrogen immersion). The same results were obtained after blanching (98% triglycerides) [30]. TLC analysis in the current study (data not shown) also indicated a major presence of triglycerides (no polyanionic group), thus implying that the interaction between proteins and lipids in this study is different.…”
Section: Yield and Puritysupporting
confidence: 84%
See 2 more Smart Citations
“…These insects were killed rapidly (30 min at − 20 °C followed by nitrogen immersion). The same results were obtained after blanching (98% triglycerides) [30]. TLC analysis in the current study (data not shown) also indicated a major presence of triglycerides (no polyanionic group), thus implying that the interaction between proteins and lipids in this study is different.…”
Section: Yield and Puritysupporting
confidence: 84%
“…Ushakova et al [29] reported 87% of lipids to be free fatty acids when the larvae were killed by freezing. Caligiani et al [30] found a free fatty acid content of 78% in larvae that were frozen. However, they stated that the storage length influenced the free fatty acids content (35% immediately after freezing, 90% after 2 months in frozen storage).…”
Section: Yield and Puritymentioning
confidence: 98%
See 1 more Smart Citation
“…As we know, the diet is the most in uential factor on the quality of black soldier y pupae meal (BSF) [5]. However, the killing method is also a highly in uential factor on BSF quality [1,[6][7][8]. Heat treatment, freezing, asphyxiation and mechanical disruption are the general procedures to euthanize black soldier y prepupae [7].…”
Section: Introductionmentioning
confidence: 99%
“…Heat treatment, freezing, asphyxiation and mechanical disruption are the general procedures to euthanize black soldier y prepupae [7]. The fast killing method with heat treatment (blanching in boiling water for a short time) has been suggested and can decrease the amount of microbial contamination, conserve nutrient quality, prevent degeneration of the end product and provide a bright colour which is acceptable to consumers, whereas slow killing methods without heat treatment (freezing, asphyxiation and blending) provided adverse consequences [6][7][8]. In contrast, Montevecchi et al [9].…”
Section: Introductionmentioning
confidence: 99%